2022
DOI: 10.1080/03637751.2022.2097284
|View full text |Cite
|
Sign up to set email alerts
|

Fighting lies with facts or humor: Comparing the effectiveness of satirical and regular fact-checks in response to misinformation and disinformation

Abstract: This study tested the effectiveness of fact-check format (regular vs. satirical) to refute different types of false information. Specifically, we conducted a pre-registered online survey experiment (N = 849) that compared the effects of regular fact-checkers and satirist refutations in response to mis-and disinformation about crime rates. The findings illustrated that both fact-checking formatsfactual and satiricalwere equally effective in lowering issue agreement and perceived credibility in response to false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
4
7
0
Order By: Relevance
“…In other words, fact-checking on its own, regardless of format, does not influence users’ evaluation of the corrections nor lends itself to more engagement with news audiences. These results are in line with past research on fact-checking formats and styles finding no fundamental benefit of using a narrative format in misinformation corrections (Ecker et al, 2020; Huang & Wang, 2022), or that corrections based on humor and satire may be as effective as factual ones (Boukes & Hameleers, 2023; Yeo & McKasy, 2021). This suggests that what really matters is correcting misinformation, not the details of its presentation, despite multiple efforts to find optimal correctives (Walter et al, 2020; however, see Carnahan & Garrett, 2020; Sangalang et al, 2019; Zheng et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In other words, fact-checking on its own, regardless of format, does not influence users’ evaluation of the corrections nor lends itself to more engagement with news audiences. These results are in line with past research on fact-checking formats and styles finding no fundamental benefit of using a narrative format in misinformation corrections (Ecker et al, 2020; Huang & Wang, 2022), or that corrections based on humor and satire may be as effective as factual ones (Boukes & Hameleers, 2023; Yeo & McKasy, 2021). This suggests that what really matters is correcting misinformation, not the details of its presentation, despite multiple efforts to find optimal correctives (Walter et al, 2020; however, see Carnahan & Garrett, 2020; Sangalang et al, 2019; Zheng et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Other lab studies found that correction tones have little to no impact. A recent work by Boukes and Hameleers (2023) investigating satirical fact-checks confirmed previous research (Hameleers and van der Meer 2020;Nyhan et al 2020;Wood and Porter 2019) and showed that different formats of fact-checks do not influence the impact of corrective information. Bode, Vraga, and Tully (2020), in their study, observed that the tone (uncivil, affirming, or neutral) applied to corrections on deceptive memes in a simulated Twitter feed did not affect the corrections' effectiveness.…”
Section: Lab Misinformation Correction Studiessupporting
confidence: 62%
“…Most misinformation correction studies involved some type of controlled lab experiments (Fridkin, Kenney, and Wintersieck 2015;Wood and Porter 2019;Ecker et al 2020;Piccolo et al 2021;Huang and Wang 2022;Velez, Porter, and Wood 2023;Boukes and Hameleers 2023). One advantage of lab experiments is that complex variables and scenarios can be investigated.…”
Section: Lab Misinformation Correction Studiesmentioning
confidence: 99%
“…Humour has been widely researched in the fields of communication and as a persuasive strategy Boukes & Hameleers, 2022;Boykoff, 2019;Boykoff & Osnes, 2019;Martin, 2006;Skurka et al, 2018). In research dissemination settings, i.e., the field of study of the present paper, Carter-Thomas and Rowley-Jolivet (2020) identify humour as one of the strategies employed in Three Minute Theses presentations to establish a relationship with the audience that becomes stimulating and appealing.…”
Section: Humour As An Engagement Strategy In Science Disseminationmentioning
confidence: 93%